Antiviral compounds from plants - Hudson, James B. (CRC Press, 1990)
This timely publication describes the botanical sources and chemical features of antiviral compounds. It covers their mechanisms of action and evaluates their therapeutic potential. Included is a discussion of synthetic analogues where appropriate. The book states that antiviral compounds in so-called medicinal plants may constitute some of their "active ingredients." It explains that many are photosensitizers, their antiviral activity dependent upon or augmented by light of specific wavelengths. This book is of value to microbiologists, phytochemists, virologists, natural-product chemists, ethnobotanists, pharmacologists, medical and veterinary researchers, and others interested in the application of plant compounds to therapy of infectious diseases.